A sodium trifluoromethanesulfinate-mediated photocatalytic strategy for aerobic oxidation of alcohols. Issue 82 (17th September 2020) - Zhu, Xianjin; Liu, Can; Liu, Yong; Yang, Haijun; Fu, Hua
Abstract : A sodium trifluoromethanesulfinate-mediated photocatalytic strategy for the aerobic oxidation of secondary and primary alcohols to ketones and carboxylic acids has been developed for the first time. Abstract : A sodium trifluoromethanesulfinate-mediated photocatalytic strategy for the aerobic oxidation of alcohols has been developed for the first time, and the photoredox aerobic oxidation of secondary and primary alcohols provided the corresponding ketones and carboxylic acids, respectively, in high to excellent yields.